Detection of frictional meltwater on snow surface using a humidity indicator - Shiraz Ahmed Siddiqui; Michael Hasler; Martin Mössner; Joost van Putten; Kurt Schindelwig; Werner Nachbauer (Current Issues in Sport Science)
Introduction & Purpose